Pelaksanaan Perilaku Hidup Bersih dan Sehat (PHBS) pada Keluarga di Dusun Kr. Raden Tanjung - Rusiana, Harlina Putri; Hidayati, Baiq Nurul; Purqoti, Dewi Nur Sukma; Romadonika, Fitri; Ilham, Ilham; Syafitri, Rias Pratiwi (Jurnal Ilmu Kesehatan Immanuel, 2021)
Perilaku Hidup Bersih dan Sehat (PHBS) is healthy behaviors on the basis of consciousness so that family members can help themselves in the field of health. Effect of the bad clean and healthy life behaviors (PHBS) are diarrhea, thypus, worming, skin disease, and poisoning.The purpose of this reserach to an overview implementation of clean and healthy life behaviors (PHBS) at households in Kr. Raden village working area Puskesmas Tanjung. Reserach design used is descriptive method and the population are 31 households. Sampling technique used is stratified random sampling and simple random sampling where the population amount is 79 households. Questionnaire used as the data collection technique.Results of this reserach, can be concluded that there are using clean water are 23 (29,1%) in good category, 42 (53,2%) in enough category, 14 (17,7%) in less category. Wash hands using clean water and soap are 11 (13,9%) in good category, 16 (20,3%) in enough category, 52 (65,8%) in less category, and using latrines healthy are 28 (35,4%) in good category, 12 (15,2%) in enough category, 39 (49,4%) in less category. And the implementation of clean and healthy life behaviors (PHBS) at family in Kr. Raden village, 24 (30,4%) in good category, 6 (7,6%) in enough category, 49 (62,0%) in less category.The conclusion reveals that most of implementation of clean and healthy life behaviors (PHBS) in the less category. Sugestion, the result of this study can be used as the knowledge addition related to the importance of clean and healthy life behaviors (PHBS) in daily living.